2021
DOI: 10.1177/11206721211012847
|View full text |Cite
|
Sign up to set email alerts
|

XEN45 real-life evaluation: Survival analysis with bleb needling and major revision outcomes

Abstract: Purpose: To evaluate real-life outcomes of XEN45 stent surgery including bleb needling (BN) and surgical bleb revision (SBR). Methods: Retrospective analysis of all XEN45 gel stents implanted in a tertiary glaucoma center with a minimum follow-up of 6 months. The main outcomes were intraocular pressure (IOP), the number of glaucoma medications, postoperative maneuvers like BN, and subsequent SBR. Success was defined as IOP ⩽ 18 and 20% reduction (criterion A), ⩽15 and 25% reduction (criterion B), and ⩽12 mmHg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Regarding safety, no patients experienced serious complications related to conventional glaucoma procedures, such as endophthalmitis, and only three cases in the MUE (10%) and one in the MCE (3.1%) group needed stent repositioning, which is a percentage similar to that described in the literature (1–12.5%) [ 19 , 39 , 41 ]. Furthermore, we found a percentage of hypotony (16% in MCE and 13% in the MUE group) that was also within the range of values (8–20%) of other studies [ 27 , 35 ]. It is worth mentioning that the cases with IOP peaks and hypotony were completely resolved in subsequent weeks with no adverse events.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding safety, no patients experienced serious complications related to conventional glaucoma procedures, such as endophthalmitis, and only three cases in the MUE (10%) and one in the MCE (3.1%) group needed stent repositioning, which is a percentage similar to that described in the literature (1–12.5%) [ 19 , 39 , 41 ]. Furthermore, we found a percentage of hypotony (16% in MCE and 13% in the MUE group) that was also within the range of values (8–20%) of other studies [ 27 , 35 ]. It is worth mentioning that the cases with IOP peaks and hypotony were completely resolved in subsequent weeks with no adverse events.…”
Section: Discussionsupporting
confidence: 89%
“…In all previous studies [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 34 , 35 , 36 ], medically controlled eyes were merged into the same group with eyes without a response to topical medication. Due to this, these studies presented methodological challenges during data analysis, such as establishing an activity indicator suitable for both situations, since some of the most frequently used criteria, such as the % of IOP reduction ( Table 5 ), are not useful indicators of responses in MCE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies reporting promising results for needling or bleb revision after XEN ® -45 implantation [28][29][30][31][32], some favoring bleb revision over needling [31,32], as we do in the case of bleb fibrosis. Studies on an older, non-marketed version of XEN ® -63 after 1-5 years of follow-up reported an IOP reduction of 18-40% and a needling rate of 0-53% [16][17][18]33].…”
Section: Needling/revision/secondary Surgerymentioning
confidence: 63%